2015
DOI: 10.1016/j.dib.2015.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Data supporting the activation of autophagy genes in the diabetic heart

Abstract: This data article contains full list of autophagy related genes that are altered in diabetic heart. This article also shows data from in vitro cultured cardiomyocytes that are exposed the high glucose treatment to simulate hyperglycemic state in vitro. The interpretation of these data and further extensive insights into the regulation of SG biogenesis by AMPK can be found in “Type-2 diabetes increases autophagy in the human heart through promotion of Beclin-1 mediated pathway” (Munasinghe et al., in press) [1]. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
(11 reference statements)
2
2
0
Order By: Relevance
“…After 4h cardiomyocytes were transfected with scrambled siRNA or beclin-1 siRNA (10pM, Qiagen) using Lipofectamine-2000 for 24h, followed by exposing the cells to high glucose (HG, 30mM) or Mannitol (NG, 30mM for osmotic control) to simulate diabetic condition in vitro for 48h. Our preliminary experiments confirmed that Beclin-1 expression peaked at 48h after high glucose treatment (Figure 1 in Ref [24]). After 48h, the efficacy of transfection was measured by Beclin-1 expression and the effect of genetic depletion of beclin-1 on autophagy was evaluated by measuring the level of LC3B-II by western blotting (as above).…”
Section: In Vitro Genetic Depletion Of Beclin-1supporting
confidence: 83%
“…After 4h cardiomyocytes were transfected with scrambled siRNA or beclin-1 siRNA (10pM, Qiagen) using Lipofectamine-2000 for 24h, followed by exposing the cells to high glucose (HG, 30mM) or Mannitol (NG, 30mM for osmotic control) to simulate diabetic condition in vitro for 48h. Our preliminary experiments confirmed that Beclin-1 expression peaked at 48h after high glucose treatment (Figure 1 in Ref [24]). After 48h, the efficacy of transfection was measured by Beclin-1 expression and the effect of genetic depletion of beclin-1 on autophagy was evaluated by measuring the level of LC3B-II by western blotting (as above).…”
Section: In Vitro Genetic Depletion Of Beclin-1supporting
confidence: 83%
“…43 Also, up-regulation of Beclin-1 by ischemiareperfusion injury stimulated autophagy 44 and activation of Beclin-1 type 2 diabetes increased cardiomyocyte autophagy. 45 In the current study, expression of Bnip3, and Beclin-1 was increased by ischemia-reperfusion injury under normoglycemia and hyperglycemia in all age groups. And hyperglycemia intensified the increased expression of Bnip3, and Beclin-1 by ischemia-reperfusion in young and middle-aged hearts, but not in old agedheart.…”
Section: Myocardial Infarction Sizesupporting
confidence: 48%
“…Therapeutic BECN1 overexpression clears mutant ataxin‐3 to alleviate Machado‐Joseph disease . Type‐2 diabetes increases BECN1 activation and autophagy in human heart, promoting progressive loss of cardiac cells . Ischemia triggers autophagy in hibernating myocardium, possibly to clear damaged organelles and unfolded proteins to support survival .…”
Section: Introductionmentioning
confidence: 99%
“…21 Type-2 diabetes increases BECN1 activation and autophagy in human heart, promoting progressive loss of cardiac cells. 22,23 Ischemia triggers autophagy in hibernating myocardium, possibly to clear damaged organelles and unfolded proteins to support survival. 24 However, during reperfusion BECN1:BCL2 interaction is increased and autophagy is attenuated, protecting the recovering myocardium from autophagic cell death.…”
Section: Introductionmentioning
confidence: 99%